Radio frequency characterization of lowpass and bandpass filters - Bayot, Aileen May E. (2004)
The research project studied and characterized the performance of lowpass and bandpass microstrip filters using different printed circuit boards at radio frequency. Through the study, the effects of using FR 4 and RO boards with the different fabrication methods were investigated. The objectives were accomplished through a combination of simulation through Microwave Office-225 (MW-225) and prototyping through milling and chemical etching. The filters were compared in terms of their frequency responses and 3 dB cut-off frequencies. The Hewlett Packard 8753C network analyzer was used to measure the filter characteristics. The General Purpose Interface Bus or GPIB and HP VEE were utilized to capture the frequency responses of the filters on the computer. Results of the actual and simulated filters were compared. Each type of filter was fabricated three times for each type of board and each fabrication method to measure the repeatability and realiability of the processes. The network analyzer was calibrated using SOLT before used in measuring. It was found out that chemical etching is the more repeatable fabrication process compared to milling. The RO 3003 60 mil board was also found out to be the best board, producing the most consistent circuits and values nearest to the simulation results.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Radio frequency; Electric filters; Electric filters, Bandpass; Microstrip filters; Lowpass filter; Network analyzer